THE USE OF AUGMENTATIVE AND ALTERNATIVE COMMUNICATION IN SURDOPEDAGOGY (International journal of artificial intelligence, 2025)
This article explores the significant role of augmentative and alternative communication (AAC) methods within surdopedagogy—the education of individuals with hearing impairments. It discusses the modern approaches and tools employed to enhance communication skills, promote social integration, and improve educational outcomes for deaf and hard-of-hearing learners. Emphasis is placed on the effectiveness of AAC strategies and technologies in supporting language development and overall learning processes.